Relationship Between Income Inequality And Economic Growth: A Comparative Analysis Of Developed And Developing Countries - Erdem Bağcı (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Economic growth is one of most important indicator in order to evaluate macroeconomic performance of countries. Thus, increase in gross domestic product, expressed as economic growth, is considered as an indicator of economic prosperity. However, despite the economic growth of countries, it is observed that income distribution equality, which is an important indicator of economic prosperity, is not provided. On the contrary, income distribution inequality is increasing day by day all over the world. In this study, the relationship between economic growth and income distribution inequality has been analyzed by examining the secondary data and literature. As a result of the study, it is concluded that economic growth is not sufficient to reduce the income distribution inequality. In addition, the problem of income distribution inequality is not only the problem of developing countries, but also the problem of developed countries. Therefore, all countries which wishing to solve this problem, should review their economic policies and adopt policies that would cover all segments of society and provide equal opportunities to all member of society. For example, in the provision of basic needs, education, health, social security and entrepreneurship, all member of the society should benefit from public facilities at an adequate level.